ANALYSIS OF CATTLE HOOF DISEASES IN THE CONDITIONS OF ENBEK LLC - Terlikbaev A.A.; Domanov D.I.; Omirali A.B. (Foundations and Trends in Modern Learning, 2024)
This article presents statistics on hoof diseases in cows that were identified at Enbek LLC and examines the main points that explain the causes of these pathologies and ways to eliminate them.